Legal Implications of Adultery: A Comparative Study of Thai and Cambodian Law - Arnee, Nonglak; Sukhum, Juntratip; Ratanak, Ith; Nuchaikaew, Teerapong (CMU Journal of Law and Social Sciences, 2025)
This study investigates the legal implications of adultery in Thailand and Cambodia, two Southeast Asian nations with shared Theravada Buddhist roots but divergent legal approaches to marital infidelity. The study aims to compare how both countries address adultery through their legal systems and examine whether these approaches align with principles of religion, culture, and international human rights. This research applies a comparative legal methodology, drawing on statutory law, court decisions, scholarly literature, and international human rights instruments, including the UDHR, ICCPR, CEDAW, CRC, and CRMW. The study also examines general comments, concluding observations, shadow reports, and opinions from legal scholars and NGOs to interpret the legal treatment of adultery. In Thailand, adultery is treated as a civil matter under the Civil and Commercial Code, allowing the aggrieved spouse to file for divorce and seek compensation for emotional distress, with no criminal penalties imposed. This approach emphasizes personal responsibility and aligns with international human rights principles. In contrast, Cambodia adopts both civil and criminal measures. Adultery is criminalized under the Law on Monogamy (2006), which includes penalties such as imprisonment and fines. These punitive measures raise concerns about state intrusion into private life, gender bias, and lack of civil compensation mechanisms for victims. The study recommends that Cambodia consider decriminalizing adultery to align with modern human rights standards. For Thailand, it proposes strengthening financial deterrents by increasing compensation under Section 1523 of the Civil and Commercial Code to better reflect the emotional and reputational harm suffered by the innocent spouse.